ANALISIS RUANG PUBLIK INSTAGRAM BEMP ILMU KOMUNIKASI UNIVERSITAS NEGERI JAKARTA SEBAGAI TRANSFORMASI INFORMASI - Febrizka Nabilla; Kiki Dwi Arviani; Rizka Herlina; Dini Safitri (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2021)
One of the important factors in delivering information transformation is the intensity of the followers. With the intensity of the followers that causes the information reported by an information submitted by the Instagram account of BEMP Communication Science, State University of Jakarta. The purpose of this study is to see the information transformation process that occurs on the BEMP Instagram account of the Jakarta State University for communication.  This research uses qualitative research methods with interview and observation data techniques. The results of this study indicate that Instagram of BEMP Communication Science, State University of Jakarta is a place for public spaces in statements of attitudes and arguments. In addition, the information transformation that occurs includes criticism and suggestions from his followers, this can happen because the information conveyed can influence the various opinions and responses of his followers, then what the followers think. The occurrence of this transformation made his followers more generous in visiting the Instagram account of BEMP Communication Science, State University of Jakarta, because they wanted information for themselves that could be obtained by visiting the Instagram account of BEMP Communication Science, State University of Jakarta.